Protected areas: A focus on Brazilian freshwater biodiversity - Azevedo-Santos, Valter M.; Frederico, Renata G.; Fagundes, Camila K.; Pompeu, Paulo S.; Pelicice, Fernando M.; Padial, André A.; Nogueira, Marcos G.; Fearnside, Philip M.; Lima, Luciano B.; Daga, Vanessa S.; Oliveira, Fagner J. M.; Vitule, Jean R. S.; et al. (Diversity & distributions, 2019)
Brazil has a variety of aquatic ecosystems and rich freshwater biodiversity, but these components have been constantly damaged by the expansion of unsustainable activities. An array of different conservation strategies is needed, especially the creation of protected areas (PAs, hereafter). However, Brazil’s PAs are biased towards terrestrial ecosystems and we argue that current PAs have limited efficacy in the protection of freshwater biodiversity. New PAs should better consider aquatic environments, covering entire basins, rivers and other freshwater habitats. We recommend ways to implement these PAs and provide guidance to avoid social impacts. Freshwater systems in Brazil provide essential goods and services but these ecosystems are being rapidly degraded and will be lost if not adequately protected.